ANALISIS PENGARUH WORK-LIFE BALANCE DAN BEBAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. RAMA MANGGALA GAS BLITAR - DIAZ ERLANGGA; I GEDE MADE SUBAGIANA; I GUSTI LANANG SUTA ARTATANAYA (GANEC SWARA, 2023)
Job satisfaction is obtained through a portion of job duties that are commensurate with the position and abilities of each employee. The company's management sets a policy for employees whose permits are in the middle of working hours for other purposes, then their work will be delegated to other employees. This interferes with the job satisfaction of other employees because their portion of work is increased. This policy is related to the work-life balance and also the workload of employees. The purpose of this study is to determine the effect of work-life balance and workload on job satisfaction of PT. Rama Manggala Gas Blitar and efforts to increase job satisfaction. The type of data used is quantitative. The sample of this study was 85 respondents using census techniques. Data analysis using the SEM-PLS method with outer and inner model measurements in SmartPLS V.3.0 software. The results of this study show that work-life balance has a significant effect on job satisfaction of PT. Rama Manggala Gas as evidenced from the results of the significance test with a t-statistic value of 7.610 > a significance level of 5% (1.96) and a p-value of 0.000 < 0.05.  Workload does not have a significant effect on the job satisfaction of PT. Rama Manggala Gas which can be seen from the t-statistical value of 1.947 < 19.6 and the p-value of 0.054 > 0.05. It is hoped that the company's management can maintain and improve the work-life balance of its employees in order to create a high level of job satisfaction